BUSCOM: RUNNING THE BUS BODY COMPANY THROUGH SWOT ANALYSIS AND BUSINESS MODEL CANVAS - Fatmawati, Elia Resha; Rahmawati, Sisca Dian; Putra, Febrianur Ibnu Fitroh Sukono; Panjaitan, Roymon; Lamidi, Lamidi; Aprilya, Dandy (Jurnal Ekonomi Manajemen, 2025)
PT. Karoseri XX is a major company specializing in bus body manufacturing. To maintain its existence amid increasing operational pressures, effective and immediately applicable strategies are required. This study aims to analyze the company’s internal and external conditions using a SWOT approach to identify key factors affecting business performance. The results of the SWOT analysis are then utilized to refine the company’s strategic plan through the Business Model Canvas (BMC) framework. This research adopts a descriptive method, with data collected through interviews and direct observations of both internal and external conditions. The findings reveal that product quality is the company’s main strength, while finishing quality remains its primary weakness. The most promising opportunity lies in the high market interest in PT. Karoseri XX’s bus body design, whereas the intensifying industry competition poses a significant threat. These results serve as a strategic foundation for the company to respond effectively to challenges and optimize market opportunities.